THE ROLE OF NATIONAL TRADITIONS IN THE EDUCATION OF PRESCHOOL CHILDREN (Web of Teachers: Inderscience Research, 2024)
Today's young generation is the true owner of their destiny, the creator of their history, the owner of their own national values, acting on the basis of our morals. This article discusses the importance of national traditions in the upbringing of preschool children.